Does More Intense Competition Lead to Higher Growth? - Dutz, Mark A. (World Bank, Washington, DC, 2014)
The relationship between the intensity of competition in an economy and its long-run growth is an open question in economics. Theoretically, there is no clear-cut answer. Empirical evidence exists, however, that in some sectors more competition leads to more innovation, and accelerates productivity growth. To complement those findings, and capture economy-wide effects, the authors conduct a cross-country study. They examine the impact on growth of various measures having to do with intensity of domestic competition - beyond the effects of trade liberalization. Their results indicate a strong correlation between long-run growth, and effective enforcement of antitrust, and competition policy.